Adequacy of financial facilities for small-medium business: empirical findings from Malaysia - Abdullah, Moha Asri; Ab. Manan, Siti Khadijah (World Business Institute, 2010)
Small-medium businesses are highly viewed as crucial towards achieving a broader economic growth and development. Many support programmes have been introduced. Although there are as many as over 14 ministries and more than 36 government agencies and institutions that are involved in providing support programs out of which many focus specifically for small businesses, the accessibility of these supports to the targeted businesses and how far small businesses make use of them are indeed difficult to ascertain. In this regard, a survey was carried out on 201 small businesses across all economic sectors in Klang Valley, Malaysia. The study reveals that the majority of businesses receive the assistance; the assistance received by businesses is also quite diverse. The finding also indicates that among small businesses whose received the financial facilities, huge proportion of them acknowledged that financial facilities provided were inadequate to their need. The paper concludes that small businesses should be viewed as highly importance with respect to providing financial and credit facilities. These funds and schemes should aim not merely at nurturing and developing the enterprises, but available and accessible in the form of soft loans, grants, equity financing and venture capital with sufficiency and reasonably cheap.